The effect of agmatine on the vascular reactivity in streptozotocin-diabetic rats - (:unkn) unknown (ACADEMIC PRESS LTD- ELSEVIER SCIENCE LTD, 2003)
Aim: We investigated the vascular effects of agmatine (decarboxylated arginine = AGM), an endogenous ligand for alpha(2)-adrenoceptors and imidazoline receptors, present in endothelium and smooth muscle, using the diabetic rat aortae. Materials and methods: Studies were performed in control group (0.2 ml i.p. saline, n = 10), streptozotocin (STZ)-diabetic control group (60 mg kg(-1) STZ i.p., n = 10), agmatine (AGM)-control group (5 mg kg(-1) day(-1) i.p. AGM for 1 month, n = 10), citrate-control group (0.2 ml 0.01 M, n = 10), insulin-treated diabetic group ((3 U kg(-1) NPH + 1 U kg(-1) regular insulin) twice per day, for 1 month, n = 10) and AGM-treated diabetic group (5 mg kg(-1) day(-1) i.p. for 1 month, n = 10). All values are expressed as means +/-S.E.M. Statistical analysis of the data was performed using ANOVA followed by Tukey multiple comparisons test. Results: One-month AGM-treatment significantly decreased the blood glucose levels of diabetic rats (502 +/- 44 mg dl(-1) to 343 +/- 31 mg dl(-1), P < 0.001). Fast, slow and total components of responses to noradrenaline in all the experimental groups were not significantly affected by AGM-treatment. AGM reversed the decreased responses of acetylcholine (pD(2) and Inh.%, P < 0.001 and P < 0.05) in diabetic rats although it did not affect the responses of sodium nitroprusside in all groups. The contraction values of KCl in all groups were not affected by AGM-treatment. Conclusion: AGM-treatment could improve the increased blood glucose level, reverse the endothelial dysfunction and normalize the endothelium-dependent relaxation responses in STZ-diabetic rats. (C) 2003 Elsevier Science Ltd. All rights reserved.
Keywords: agmatine; diabetes; vascular reactivity; streptozotocin; SMOOTH-MUSCLE; NITRIC-OXIDE; EXTRACELLULAR CALCIUM; ALPHA ADRENOCEPTORS; ENDOTHELIUM; AORTA; CONTRACTION; RESPONSES; INSULIN; RELAXATION